A composite phase change material with magnetothermal conversion performance and preparation method thereof

By chemically etching the ZIF-67 template in composite phase change materials, it is solved by synthesizing uniformly distributed magnetic nanoparticles and compounding them with the phase change core material, and the uneven performance problem caused by magnetic nanoparticles agglomeration is solved, and the thermal conductivity of the material is improved Rate and magneto-heat conversion performance.

CN115851241BActive Publication Date: 2025-02-14SUZHOU RONGGEJUN NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211654096.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-02-14
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

In existing composite phase change materials, magnetic nanoparticles are prone to agglomeration, resulting in uneven magnetic properties, mechanical properties and heat transfer properties, affecting their magneto-heat conversion properties.

Method used

Using ZIF-67 as a template, a layered bimetal hydroxide with uniformly distributed magnetic elements was synthesized by chemical etching, and in situ reduction under a reducing atmosphere to obtain a phase change carrier of uniformly dispersed magnetic nanoparticles, followed by phase change. The core material is composited to form a composite phase change material with magneto-heat conversion performance.

Benefits of technology

It effectively avoids the uneven performance problem caused by magnetic nanoparticles agglomeration, improves the thermal conductivity and magneto-heat conversion performance of composite phase change materials, and realizes rapid storage and release of heat.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115851241B_ABST
    Figure CN115851241B_ABST
Patent Text Reader

Abstract

The present application discloses a composite phase change material with magnetothermal conversion performance and a preparation method thereof. The preparation method comprises the following steps: Step 1, using ZIF‑67 as a template, chemically etching it with different metal salts to obtain a layered double metal hydroxide with uniform distribution of magnetic metal elements; Step 2, calcining under a reducing atmosphere, so that the magnetic metal elements in the layered double metal hydroxide with uniform distribution of magnetic elements are in situ reduced to magnetic nanoparticles, and a phase change carrier with uniformly dispersed magnetic nanoparticles is obtained; Step 3, compounding the phase change carrier with the phase change core material. The present application cleverly and effectively solves the problem of agglomeration of magnetic nanoparticles, thereby avoiding the phenomena of uneven mechanics, magnetism and heat transfer caused by it. At the same time, the uniformly distributed magnetic nanoparticles in the present application can shorten the heat transfer path and improve the thermal conductivity of the composite phase change material with magnetothermal conversion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite phase change materials, and more specifically, to a composite phase change material with magnetothermal conversion performance and a preparation method thereof. Background Art

[0002] With the rapid development of industrialization, while mineral energy (such as coal, natural gas, oil, etc.) is facing the crisis of depletion, the environmental pollution problem it brings is becoming more and more serious. Therefore, it is crucial to improve energy efficiency and develop new energy (such as solar energy, magnetic energy, biomass energy, etc.). At present, wind energy, solar energy, ocean energy, etc. have been widely used in power systems and related fields such as heating. Magnetic energy, as a clean energy, converts magnetic energy into thermal energy for industrial production through magnetocaloric effect, which is an effective way to solve the energy crisis. Combining magnetic nanoparticles with phase change materials to prepare composite phase change materials, and using composite phase change materials to store and release thermal energy can effectively solve the spatial and temporal mismatch between thermal energy supply and demand, and is also one of the important means to improve energy efficiency.

[0003] Patent CN110358504A discloses a method for preparing a wood-based functional magnetothermal composite phase change heat storage material. Patent CN106010458A discloses a polymer nanocomposite phase change energy storage material for magnetothermal-photothermal dual-drive energy conversion and storage and a method for preparing the same. However, the composite phase change materials disclosed above are to directly add magnetic oxides to carrier materials, or to synthesize magnetic oxides in solution. However, due to the large magnetic force between magnetic particles, agglomeration will inevitably occur when they are directly added or directly synthesized in solution, thereby affecting the magnetic properties of the magnetic nanocomposite material. Therefore, in order to obtain magnetic nanocomposites with excellent performance, avoiding agglomeration of magnetic nanoparticles is an essential and important condition. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present application provides a composite phase change material with magnetothermal conversion performance and a preparation method thereof. The present application uses ZIF-67 as a template, chemically etches it to synthesize a layered double metal hydroxide with uniform distribution of magnetic elements, and in-situ reduces it under a reducing atmosphere to obtain a phase change carrier with uniformly dispersed magnetic nanoparticles; and then composites it with a phase change core material to form a composite phase change material with magnetothermal conversion performance. The present application cleverly and effectively solves the problem of agglomeration of magnetic nanoparticles, thereby avoiding the mechanical, magnetic and heat transfer unevenness caused by it. At the same time, the uniformly distributed magnetic nanoparticles in the present application can shorten the heat transfer path and improve the thermal conductivity of the composite phase change material.

[0005] In order to achieve the above objectives, in a first aspect, the present application provides a method for preparing a composite phase change material having magnetothermal conversion performance, comprising the following steps:

[0006] Step 1: Using ZIF-67 as a template, chemically etching it with different metal salts to obtain a layered double hydroxide with uniform distribution of magnetic metal elements;

[0007] Step 2: calcining in a reducing atmosphere to reduce the magnetic metal elements in the layered double hydroxide with uniform magnetic element distribution to magnetic nanoparticles in situ, thereby obtaining a phase change carrier with uniformly dispersed magnetic nanoparticles;

[0008] Step 3: Compounding the phase change carrier and the phase change core material.

[0009] Furthermore, the specific method of step 1 is:

[0010] Step 1.1: Using Co(NO3)2 and 2-methylimidazole (2-MIM) as precursors, dodecahedral ZIF-67 was synthesized by standing in methanol at room temperature for 12 to 24 hours;

[0011] Step 1.2: Dissolve ZIF-67 in ethanol solution (concentration of 2.5-14 g / L), and dissolve different types of metal salts in deionized water (concentration of 1.5-30 g / L), and perform ultrasonic treatment for 5-15 minutes respectively;

[0012] Step 1.3: The two solutions in step 1.2 which are evenly dispersed are then mixed and reacted at 60 to -80°C for 15 minutes to 24 hours to obtain a layered double hydroxide with evenly distributed magnetic metal elements.

[0013] Furthermore, the metal salt includes one or more of iron salt, molybdenum salt and nickel salt; the layered double hydroxide includes one or more of Mo-Co LDH, Ni-Co LDH and Fe-Co LDH.

[0014] Furthermore, the specific method of step 2 is: placing the layered double hydroxide with uniform distribution of magnetic metal elements obtained in step 1 in a crucible, heating it at 300-450°C for 2-3 hours at a heating rate of 1-2°C / min under a reducing atmosphere, and cooling it to room temperature to obtain a phase change carrier with uniformly dispersed magnetic nanoparticles.

[0015] Preferably, the reducing atmosphere is a mixed atmosphere of 5% hydrogen and 95% argon.

[0016] Furthermore, the specific method of step 3 is: vacuum the phase change carrier prepared in step 2 at 80°C to 120°C for 4 hours, then disperse it in a solution containing the phase change core material, heat it to 25 to 100°C, stir it for 1 to 24 hours, and then filter it, and finally place it in a 50 to 120°C oven to dry for 2 to 24 hours.

[0017] Furthermore, the phase change core material includes polyol and fatty acid.

[0018] Preferably, the polyol includes one or more of polyethylene glycol 1000-20000, pentaerythritol, and neopentyl glycol; the fatty acid includes one or more of stearic acid, myristic acid, palmitic acid, capric acid, lauric acid, pentadecanoic acid, and sebacic acid.

[0019] Furthermore, the solution containing the phase change core material is an aqueous solution or an alcohol solution; the concentration of the solution containing the phase change core material is 10-15 g / L, and the loading amount of the composite phase change material is 50-80%.

[0020] In a second aspect, the present invention provides a composite phase change material with magnetothermal conversion performance, which is prepared by the above-mentioned preparation method.

[0021] The technical solution provided by this application has at least the following beneficial effects compared with the prior art:

[0022] 1) The preparation method of the composite phase change material with magnetothermal conversion performance provided by the present application is to use ZIF-67 as a template, chemically etch it to synthesize a layered double metal hydroxide with uniform distribution of magnetic elements, and in-situ reduce it under a reducing atmosphere to obtain a phase change carrier with uniformly dispersed magnetic nanoparticles; and then compound it with a phase change core material to form a composite phase change material with magnetothermal conversion performance. The present application cleverly solves the problem that magnetic nanoparticles in the phase change carrier are easy to agglomerate, and avoids the mechanical, magnetic and heat transfer unevenness caused by the agglomeration of nanoparticles;

[0023] 2) The composite phase change material with magnetothermal conversion performance provided by the present application has uniformly distributed magnetic nanoparticles that provide a channel for heat transfer, shorten the heat transfer path, and can effectively improve the thermal conductivity of the composite phase change material, thereby achieving rapid storage and release of heat;

[0024] 3) The layered double metal hydroxide and phase change core material used in the preparation method of the present application are diverse in selection and have good economic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM photo of the Mo-Co LDH obtained in Example 1 of the present invention;

[0026] Figure 2 This is a SEM photo of the phase change carrier obtained in Example 1 of the present invention;

[0027] Figure 3 This is a SEM photograph of the Ni-Co LDH obtained in Example 2 of the present invention. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to understand the present application more clearly, the present application is further described in detail below in conjunction with examples and drawings. However, it should be understood that the following examples are only preferred implementation methods of the present application, and the scope of protection required by the present application shall be based on the scope defined in the claims.

[0029] <Example>

[0030] Example 1

[0031] A method for preparing a composite phase change material with magnetothermal conversion performance comprises the following steps:

[0032] Step 1. Use Co(NO3)2 and 2-methylimidazole (2-MIM) as precursors, stand in methanol at room temperature for 24 hours to synthesize dodecahedral ZIF-67; take 0.2g of ZIF-67 and dissolve it in 80mL of ethanol solution to obtain solution A, take 0.06g of (NH4)6Mo7O4 and dissolve it in 20mL of deionized water solution to obtain solution B, ultrasonicate for 5min respectively, pour solution B into solution A and ultrasonicate for 1min to mix them evenly, then pour the solution into a round-bottom flask, react at 85℃ for 15min under condensation reflux conditions, cool to room temperature, centrifuge and wash with ethanol and deionized water several times, and dry at 60℃ for 24h to obtain a layered double metal hydroxide (Mo-Co LDH) with uniform distribution of magnetic metal elements. The SEM photo of Mo-Co LDH is shown in Figure 1 shown.

[0033] Step 2: Take 0.150 g of the Mo-Co LDH prepared in step 1 and put it into a crucible. Heat it to 450°C at a rate of 2°C / min in a mixed gas containing 5% H2 and 95% Ar, and keep it at 450°C for 2 hours to obtain a phase change carrier with uniformly dispersed magnetic nanoparticles. The SEM photo of the phase change carrier is shown in Figure 2 shown.

[0034] Step 3: Take 0.150 g of the phase change carrier prepared in step 2 and evacuate it at 120°C for 4 hours to remove small molecules in the pores; then disperse it in 10 mL of anhydrous ethanol solution containing 0.35 g of myristic acid (MA), stir it at 60°C for 2 hours, place the mixture in an 80°C drying oven, keep it warm for 24 hours, and collect the composite phase change material with magnetothermal conversion performance.

[0035] Example 2

[0036] A method for preparing a composite phase change material with magnetothermal conversion performance comprises the following steps:

[0037] Step 1. Use Co(NO3)2 and 2-methylimidazole (2-MIM) as precursors, stand in methanol at room temperature for 24 hours to synthesize dodecahedral ZIF-67; take 0.35g of ZIF-67 and dissolve it in 80mL of ethanol solution to obtain solution A, take 0.15g of Ni(NO3)2 and dissolve it in 5mL of deionized water solution to obtain solution B, ultrasonicate for 5min respectively, pour solution B into solution A and ultrasonicate for 1min to mix them evenly, then pour the solution into a round-bottom flask, react at 80℃ for 6h, cool to room temperature, centrifuge and wash with ethanol and deionized water several times, and dry at 60℃ for 24h to obtain a layered double metal hydroxide (Ni-Co LDH) with uniform distribution of magnetic metal elements. The SEM photo of Ni-Co LDH is shown in Figure 3 shown.

[0038] Step 2: Take 0.150 g of Mo prepared in step 1 Ni -Co LDH was placed in a crucible, heated to 450°C at a rate of 2°C / min in a mixed gas containing 5% H2 and 95% Ar, and kept at 450°C for 2h to obtain a phase change carrier with uniformly dispersed magnetic nanoparticles.

[0039] Step 3: Take 0.150 g of the phase change carrier prepared in step 2 and evacuate it at 120°C for 4 hours to remove small molecules in the pores; then disperse it in 10 mL of anhydrous ethanol solution containing 0.35 g of myristic acid (MA), stir it at 60°C for 2 hours, place the mixture in an 80°C drying oven, keep it warm for 24 hours, and collect the composite phase change material with magnetothermal conversion performance.

[0040] Example 3

[0041] A method for preparing a magnetocaloric composite phase change material comprises the following steps:

[0042] Step 1, using Co(NO3)2 and 2-methylimidazole (2-MIM) as precursors, standing in methanol at room temperature for 24 hours, synthesizing dodecahedral ZIF-67; taking 0.2g of ZIF-67 and dissolving it in 15mL of ethanol solution to obtain solution A, taking 0.15g of Fe(NO3)3 and dissolving it in 5mL of deionized water solution to obtain solution B, respectively ultrasonically treating for 5min, pouring solution B into solution A and ultrasonicating for 1min to mix them evenly, then pouring the solution into a round-bottom flask, and adjusting the pH to 10 with NaOH and NaCO3, stirring for 30min. Then react at 65℃ for 24h, cool to room temperature, centrifuge and wash with ethanol and deionized water several times, and dry at 70℃ for 12h to obtain a layered double metal hydroxide (Fe-Co LDH) with uniform distribution of magnetic metal elements.

[0043] Step 2: Take 0.150 g of the Fe-Co LDH prepared in step 1 and put it into a crucible. Heat it to 350°C at a rate of 2°C / min in a mixed gas containing 5% H2 and 95% Ar, and keep it at 350°C for 3 hours to obtain a phase change carrier with uniformly dispersed magnetic nanoparticles.

[0044] Step 3: Take 0.150 g of the phase change carrier prepared in step 2 and evacuate it at 120°C for 4 hours to remove small molecules in the pores; then disperse it in 10 mL of anhydrous ethanol solution containing 0.15 g PEG10000, stir it at 60°C for 2 hours, place the mixture in an 80°C drying oven, keep it warm for 12 hours, and collect the composite phase change material with magnetothermal conversion performance.

[0045] Comparative Example 1

[0046] Step 1, using Co(NO3)2 and 2-methylimidazole (2-MIM) as precursors, standing in methanol at room temperature for 24 hours to synthesize dodecahedral ZIF-67; taking 0.2g of ZIF-67 and dissolving it in 80mL of ethanol solution to obtain solution A, taking 0.06g of (NH4)6Mo7O4 and dissolving it in 20mL of deionized water solution to obtain solution B, ultrasonicating for 5min respectively, pouring solution B into solution A and ultrasonicating for 1min to mix them evenly, then pouring the solution into a round-bottom flask, reacting at 85℃ for 15min under condensation reflux conditions, cooling to room temperature, centrifuging and washing with ethanol and deionized water several times, and drying at 60℃ for 24h to obtain LDH (Mo-Co LDH) with uniform distribution of different metal elements;

[0047] Step 2: Take 0.150 g of the Mo-Co LDH prepared in step 1 and put it into a beaker, and dissolve it in 30 ml of deionized water; take 0.053 g of Co element and add it to the aqueous solution of Mo-Co LDH, stir it at room temperature for 3 hours, wash it with deionized water by centrifugation several times, and dry it at 60°C for 24 hours to obtain a phase change carrier of nanoparticles and LDH physically mixed.

[0048] Step 3: Take 0.150 g of the phase change carrier prepared in step 2 and evacuate it at 120°C for 4 hours to remove the small molecules in the pores; then disperse it in 10 mL of n-hexane solution containing 0.35 g of paraffin (PW), stir it at 60°C for 2 hours, place the solution in an 80°C drying oven, keep it warm for 24 hours, and collect the composite phase change material of the physical mixture of magnetic nanoparticles and LDH.

[0049] Compared with Example 1, since the directly added magnetic nanoparticles occupy part of the pores of the carrier material, the enthalpy value of the composite phase change material of Comparative Example 1 is lower than that of the composite phase change material of Example 1, which is not conducive to the utilization and storage of energy.

[0050] The above-mentioned specific embodiments of the present application are merely preferred embodiments for explaining the present application, and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications without creative contribution as needed. However, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a composite phase change material with magnetothermal conversion performance, characterized in that: The following steps are involved: Step 1, using ZIF-67 as a template, chemically etching it with a metal salt to obtain a layered double hydroxide with uniform distribution of magnetic metal elements; the metal salt includes one or more of an iron salt, a molybdenum salt and a nickel salt, and the layered double hydroxide includes one or more of Mo-Co LDH, Ni-Co LDH and Fe-Co LDH; Step 2: calcining in a reducing atmosphere to reduce the magnetic metal elements in the layered double hydroxide with uniform magnetic element distribution to magnetic nanoparticles in situ, thereby obtaining a phase change carrier with uniformly dispersed magnetic nanoparticles; Step 3: Compound the phase change carrier and the phase change core material.

2. The method for preparing a composite phase change material with magnetothermal conversion performance according to claim 1, characterized in that: The specific method of step 1 is: Step 1.1: Using Co(NO3)2 and 2-methylimidazole as precursors, dodecahedral ZIF-67 was synthesized by standing in methanol at room temperature for 12 to 24 hours; Step 1.2: Dissolve ZIF-67 in ethanol solution and metal salt in deionized water, and ultrasonically treat each for 5 to 15 minutes; Step 1.3: The two solutions in step 1.2 which are evenly dispersed are then mixed and reacted at 60-80° C. for 15 min-24 h to obtain a layered double hydroxide with evenly distributed magnetic metal elements.

3. The method for preparing a composite phase change material with magnetothermal conversion performance according to claim 1, characterized in that: The specific method of step 2 is: placing the layered double hydroxide with uniform distribution of magnetic metal elements obtained in step 1 in a crucible, heating it at 300-450°C for 2-3 hours at a heating rate of 1-2°C / min under a reducing atmosphere, and cooling it to room temperature to obtain a phase change carrier with uniformly dispersed magnetic nanoparticles.

4. The method for preparing a composite phase change material with magnetothermal conversion performance according to claim 3, characterized in that: The reducing atmosphere is a mixed atmosphere of 5% hydrogen and 95% argon.

5. The method for preparing a composite phase change material with magnetothermal conversion performance according to claim 1, characterized in that: The specific method of step 3 is: vacuum the phase change carrier prepared in step 2 at 80℃~120℃ for 4h, then place it in a solution containing the phase change core material, heat it to 25~100℃, stir it for 1~24h and then filter it, and finally place it in a 50~120℃ oven to dry for 2~24h.

6. The method for preparing a composite phase change material with magnetothermal conversion performance according to claim 1, characterized in that: The phase change core material includes polyol and fatty acid.

7. The method for preparing a composite phase change material with magnetothermal conversion performance according to claim 6, characterized in that: The polyol includes one or more of polyethylene glycol 1000-20000, pentaerythritol and neopentyl glycol; the fatty acid includes one or more of stearic acid, myristic acid, palmitic acid, capric acid, lauric acid, pentadecanoic acid and sebacic acid.

8. The method for preparing a composite phase change material with magnetothermal conversion performance according to claim 5, characterized in that: The solution containing the phase change core material is an aqueous solution or an alcohol solution; the concentration of the phase change core material solution is 10-15 g / L, and the loading amount of the composite phase change material is 50-80%.

9. A composite phase change material with magnetothermal conversion performance, characterized in that: The preparation method is described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Magnetic thermal-photothermal double-drive energy conversion and storage polymer nano composite phase-change energy-storage material and preparation method thereof

    CN106010458A

  • Preparation method of wood-based functional magneto-thermal composite phase change heat storage material

    CN110358504A

  • Method for preparing multilevel porous carbon base composite phase change material

    CN104710965A

  • Preparation method of three-dimensional (3D) porous carbon skeleton-based composite phase change material

    CN106190041A

  • Metal organic framework derived carbon-based photo-thermal phase change energy storage material as well as preparation method and application thereof

    CN114410279A